Mapping our Digital Dilemmas: Assessing Harms and the Viability of Legislation and Regulation in the United States - Martha Garcia-Murillo; Ian MacInnes (International Telecommunications Society (ITS), 2024)
The rapid evolution of information technologies has led to a society with worldwide connectivity, efficiency, and convenience. Yet these technological innovations are not free of perils, as they can also negatively impact our economic, political, and social well-being. This paper analyzes the tradeoffs between technological progress and its potential harms, particularly in the United States. Recognizing the historical benefits of digital technologies while also being mindful of their negative consequences, we highlight the complex market dynamics, political influences, and societal forces that determine whether policymakers can pass legislation and regulatory measures to mitigate the potential harm caused by disruptive innovations. The research question driving this paper is: How do market dynamics, political influences, and societal forces interact to shape the prospects of introducing effective legislation and regulatory measures for digital technologies in the United States? In the absence of legal frameworks, what alternative entities are there to mitigate a technology's negative impacts? The research methodology entailed a comprehensive analysis of the scholarly literature and a review of secondary sources related to digital technologies. Synthesizing insights from academic works, reports, and studies, this paper analyzes the multifaceted forces influencing the introduction of legislation and regulatory frameworks for digital technologies in the United States.
Keywords: 330; Digital regulation; social media; digital markets; algorithms; artificial intelligence